Improved Clinical and Functional Outcomes in Crouch Gait Following Minimally Invasive Hamstring Lengthening and Serial Casting in Children With Cerebral Palsy. Issue 6 (July 2020) - Long, Jason T.; Cobb, Leah; Garcia, Micah C.; McCarthy, James J.
Abstract : Background: Serial extension casting represents a novel solution for addressing residual knee flexion contractures following hamstring lengthening in children with cerebral palsy. The purpose of this study was to investigate postoperative changes in patients following hamstring lengthening with a serial casting protocol. Methods: Measures from preoperative and postoperative gait analyses were reviewed retrospectively for 19 patients with cerebral palsy who underwent hamstring lengthening followed by serial extension casting. Postoperative changes in clinical, functional, and kinematic parameters were assessed using paired parametric methods. Results: Improvements were measured in popliteal angle, knee contracture, peak stance phase knee extension, sagittal plane range of motion of the knee during walking, Gait Deviation Index, and pediatric outcomes data collection instrument Global score. Nearly 80% of the cohort (15/19 patients) demonstrated a significant or moderate response to the intervention, whereas 20% demonstrated no improvement. Of note, significantly increased anterior pelvic tilt was also observed. Conclusions: Hamstring lengthening combined with a serial casting protocol was associated with significant postoperative improvements in a range of clinical (eg, knee contracture), functional (eg, pediatric outcomes data collection instrument Global), and kinematic (eg, knee extension in stance) parameters. Improvements following this minimally invasive surgery were comparable to outcomes from procedures with higher complication rates. Level of Evidence: This is a Level III Therapeutic Study (retrospective study investigating the results of a treatment).